Mixed shear mode and compression mode magnetorheological elastomer isolator - Azman A.N.; Jaafar M.F. (American Institute of Physics Inc., 2023)
The work presents the investigation on mixed mode MRE isolator to study the behavior of the smart magnetorheological elastomer (MRE) material. The study involves from the fabrication of the samples to the testing of the complete isolator. The fabrication of the MRE samples is also important to show the necessary materials and tools needed to produce a sample that is applicable for a both shear and compression testing. The casing for the isolator as well as the mould are produced beforehand to allow flexibility and more time to focus on the items needed for the fabrication process. Once the casing and samples are well integrated, the complete MRE isolator will go through the testing process. NI LabVIEW NXG 5.0 is the software used to receive data from the testing equipment and from there onwards, the data are manipulated for comparisons. The comparison of the graphs will then be related to the previous studies to allow a deeper understanding on the project. 2021 Author(s).